Estimation Genetic Parameter and Selection of Yield Components in Two Population F2 Bird Pepper (Capsicum frutescens L) - Hakim, Abdul; Syukur, Muhammad; EK, Yudiwanti Wahyu (Universitas Sembilanbelas November Kolaka, 2023)
Bird pepper (Capsicum frutescens L.) is one of the main commodities of horticulture in Indonesia. The process of assembling bird pepper was done by selected from the segregation population. This study aimed to obtain selected plant candidates in the F2 population by index selection on the character of the yield components on bird pepper. The results of this study showed that in population F2-285290 the correlation value showed a very significant significance for all characters on the yield component character while in the population F2-321290 only fruit thickness and fruit stalk length were not significantly correlated. The broad mean heritability value in the high category of the two populations were in fruit weight, fruit length, fruit diameter and fruit stalk length. The results of index selection in the population F2-285290 with a selection intensity 10 percent obtained by selected plants as many as 20 best plants, namely plants no 16, 30, 31, 36, 43, 50, 65, 80, 82, 102, 123, 134, 153, 190, 216, 244, 245, 263, 273 and 290 while in populations F2-321290 selected plants are no. 18, 21, 23, 30, 32, 37, 42, 154, 155, 162, 165, 167, 180, 185, 199, 220, 221, 230, 228 and 229